2012
DOI: 10.1103/physreva.85.032304
|View full text |Cite
|
Sign up to set email alerts
|

Partially random phase attack to the practical two-way quantum-key-distribution system

Abstract: Phase randomization is a very important assumption in the Bennett-Brassard 1984 quantum key distribution (QKD) system with a weak coherent source. Thus an active phase modulator is needed to randomize the phase of source. However, it is hard to check whether the phase of source is randomized totally or not in practical QKD systems. In this paper a partially random phase attack is proposed to exploit this imperfection. Our analysis shows that Eve can break the security of a two-way QKD system by using our attac… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
27
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(27 citation statements)
references
References 36 publications
0
27
0
Order By: Relevance
“…Furthermore, for a coherent state |α , the probability distribution of the measured result of homodyne detection can be written as [9]…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, for a coherent state |α , the probability distribution of the measured result of homodyne detection can be written as [9]…”
Section: Methodsmentioning
confidence: 99%
“…Quantum key distribution (QKD) 1 admits two remote parties (Alice and Bob) to share unconditional secure key based on the principle of quantum mechanics 2 3 , which has been demonstrated in experiments with long distance and high repetition rate 4 5 6 7 . However, the practical QKD system will suffer from quantum hacking due to device imperfections 8 9 10 11 12 13 14 15 , then the unconditional security of QKD is compromised. In practical QKD systems based on BB84 protocol, the weak coherent source (WCS) is often used to replace the single photon source which is unavailable within current technology.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that when the phase is not randomized, the performance will be substantially reduced with a strict security proof [20]. In fact, there are experimental quantum hacking demonstrations showing that a QKD system may be attacked when the phase is not randomized [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…Finally, a type of light injection attack that affects the operation of the laser diode in the transmitter has recently been introduced, allowing Eve to actively derandomise the source's phase and even change other parameters [54]. Indeed, the use of non-phase-randomised signals has a severe effect on the security of QKD, as has been shown in the past decade [55][56][57][58].…”
Section: Introductionmentioning
confidence: 99%